School Principal Leadership Style In Improving Teacher Performance In Elementary School Muhammadiyah Purbayan Yogyakarta - Wahid Hasim; Reza Ariefka; Krisno Budi Prasetyo; Romlan Romlan (Jurnal Lentera Pedagogi, 2024)
The style or manner of a school principal in his capacity as a leader largely determines the success of improving the performance of teachers under his leadership. The purpose of this study was to obtain data on (1) the principal's leadership style in improving work discipline, (2) the principal's leadership style in increasing teacher work motivation, (3) the principal's leadership style in increasing responsibility and (4) the constraints- obstacles faced by school principals in improving teacher performance. Through a qualitative approach with descriptive methods, data collection techniques are carried out through interviews, observations, and documentation. This research shows that (1) the principal applies the situational leadership style in increasing discipline, (2) the principal applies the managerial leadership style in increasing teacher work motivation, (3) the principal applies the managerial leadership style in increasing teacher responsibility, and (4 ) constraints faced by the principal, namely the low teacher in the use of "computer" technology, the selection of learning methods and the different background conditions of subordinates. It is recommended that the principal can apply a better or varied leadership style so that the desired goals can be achieved well and optimally